2008
DOI: 10.1007/s10620-008-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Fluvastatin on Liver Microcirculation and Regeneration After Massive Hepatectomy in Rats

Abstract: Fluvastatin, the first entirely synthetic statin, has a significant cholesterol-lowing effect comparable with other statins. In addition, it has been shown to inhibit oxidative stress and improve vascular endothelial function. The aim of this study was to clarify the pretreatment effects of fluvastatin on liver function after massive hepatectomy in rats. Six-week-old male Wister rats were divided into two groups: a fluvastatin group (group F), pretreated with oral administration of fluvastatin (20 mg/kg per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Original magnification 9100 rats [19]. Previous studies have shown that several factors, such as growth factors, nutritional status, pharmacologic agents, etc., may affect liver regeneration in rats [20,21]. In the present study, bicyclol pretreatment significantly enhanced liver regenerative capacity as indicated by increased liver regeneration rate, PCNA label index, and proliferation index.…”
Section: Discussionsupporting
confidence: 55%
“…Original magnification 9100 rats [19]. Previous studies have shown that several factors, such as growth factors, nutritional status, pharmacologic agents, etc., may affect liver regeneration in rats [20,21]. In the present study, bicyclol pretreatment significantly enhanced liver regenerative capacity as indicated by increased liver regeneration rate, PCNA label index, and proliferation index.…”
Section: Discussionsupporting
confidence: 55%
“…Statins have been shown to suppress inflammation and proliferation in vascular endothelial and smooth muscle cells [8,39] and to reduce I/R injury in the liver [8] and the kidney [40]. Of interest, the pleiotropic actions of statins are not related to its lipid-lowering mechanism but rather caused by their anti-oxidative properties [17,41], their inhibitory action on leukocyte adhesion [42,43], and their modulatory function on the microcirculation [42,44]. These statin actions may have contributed to the prevention of I/R injury observed in the present study after MDDP application.…”
Section: Discussionmentioning
confidence: 99%
“…This is also clinically applicable because statins are potent stimuli for NO production in sinusoidal endothelial cells (Deleve et al, 2008;Tokunaga et al, 2008), and adjacent HSCs are likely to be exposed to high concentrations of NO. Therefore, in vivo evaluation of 17AAG/statin combination is anticipated as an antifibrotic strategy.…”
Section: Discussionmentioning
confidence: 99%